2014
DOI: 10.1039/c4lc00371c
|View full text |Cite
|
Sign up to set email alerts
|

Body-on-a-chip simulation with gastrointestinal tract and liver tissues suggests that ingested nanoparticles have the potential to cause liver injury

Abstract: The use of nanoparticles in medical applications is highly anticipated, and at the same time little is known about how these nanoparticles affect human tissues. Here we have simulated the oral uptake of 50 nm carboxylated polystyrene nanoparticles with a microscale, body-on-a-chip system (also referred to as multi-tissue microphysiological system or micro Cell Culture Analog). Using this system, we combined in vitro models of the human intestinal epithelium, represented by a co-culture of enterocytes (Caco-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
204
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(212 citation statements)
references
References 36 publications
4
204
0
Order By: Relevance
“…3B) as well as the combination of iPSC and organ-on-a-chip technology are technically demanding, but holds great promise for the future of inhalation toxicology. An example of the usefulness of such an body-on-achip approach is described by Esch and co-workers, who demonstrated that "ingested" nanoparticles that were absorbed through a gastrointestinal chip could cause injury to cells in a linked liver chip (Esch et al, 2014).…”
Section: Organ-on-a-chip Models and Microfluidicsmentioning
confidence: 99%
“…3B) as well as the combination of iPSC and organ-on-a-chip technology are technically demanding, but holds great promise for the future of inhalation toxicology. An example of the usefulness of such an body-on-achip approach is described by Esch and co-workers, who demonstrated that "ingested" nanoparticles that were absorbed through a gastrointestinal chip could cause injury to cells in a linked liver chip (Esch et al, 2014).…”
Section: Organ-on-a-chip Models and Microfluidicsmentioning
confidence: 99%
“…Furthermore, skin and lung models may be exposed at the airliquid interface (Stoehr et al 2015) while ingestion models could include a more realistic digestion fluid on one side. Finally, cell models are being refined, and new developments such as microfluidic systems and organoids promise to allow more realistic models and to eliminate the species differences in toxicological data by using human cells (Esch et al 2014;Tralau et al 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While the field of tissue engineering remains influenced by the original expectation that ''the more complex the tissue the better,'' this intuition is not necessarily true, particularly for in vitro modeling work. Whether studying responses to a specific environmental factor (such as drug, hypoxia or inflammation) using a single or multi-tissue device, [68][69][70][71] the purpose of a platform should be to make the simplest system that has a desired functional readout. The complexity of an individual tissue type or the necessary combination of multiple tissue types will naturally depend on the factor being studied.…”
Section: Discussionmentioning
confidence: 99%